2022
DOI: 10.47565/ndthdt.2022.57
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiyaliz Hastalarında Yorgunluk, Bakım Bağımlılığı ve Etkileyen Faktörlerin İncelenmesi/ Investigation of Fatigue, Care Dependence and Affecting Factors in Hemodialysis Patients

Abstract: Amaç: Araştırma, hemodiyaliz hastalarının yorgunluk, bakım bağımlılığı ve etkileyen faktörlerin belirlenmesi amacıyla yapıldı. Gereç ve Yöntemler: Araştırma, Aralık 2021-Ocak 2022 tarihleri arasında Adıyaman Üniversitesi Eğitim ve Araştırma Hastanesi diyaliz ünitesinde tedavi gören, araştırmaya alınma kriterlerine uyan 70 hasta ile tanımlayıcı olarak yapıldı. Araştırmanın verileri; “Kişisel Bilgi Formu”, “Yorgunluk Şiddet Ölçeği” ve “Bakım Bağımlığı Ölçeği” ile toplandı. Verilerin istatistiksel analizinde sayı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…(2022) it was discerned that the individuals aged 65 years or above were more dependent on their daily life activities than the individuals from the groups aged below 65 years. Likewise, in numerous research studies, the relationship between age and dependence was analyzed, and similar results were obtained (Özbudak & Oksay Şahin, 2021;Güler et. al., 2022).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…(2022) it was discerned that the individuals aged 65 years or above were more dependent on their daily life activities than the individuals from the groups aged below 65 years. Likewise, in numerous research studies, the relationship between age and dependence was analyzed, and similar results were obtained (Özbudak & Oksay Şahin, 2021;Güler et. al., 2022).…”
Section: Discussionsupporting
confidence: 55%
“…In the research conducted by Güler et al (2022) with the hemodialysis patients, it was ascertained that the majority of the participant patients were dependent on another person in daily life activities. The study by Sungur et al (2009) found that, even if the individuals with chronic renal failure mostly performed daily life activi-ties adequately, they could not find effective solutions to the problems experienced at home after the hemodialysis therapy, they were dependent on another person in the home setting, incapable of applying to health facilities, and needed to acquire information and support for the care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of Güler et al, the mean BDI score of the physically disabled group is 56.53±14.46 and they need more care. 31 As the physical disability of the patient increases, the dependency on the caregiver increases. 32 96.6% of individuals with speech problems and 91.5% of individuals with walking problems constitute the group with high care dependency.…”
Section: Discussionmentioning
confidence: 99%